2005
DOI: 10.1111/j.1439-0426.2005.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, seasonal and diel distribution patterns of two species of mojarras (Pisces: Gerreidae) in a Mexican tropical coastal lagoon

Abstract: Spatial, seasonal and diel distribution patterns were analysed over a 2-year period for Diapterus auratus and Eucinostomus melanopterus in Pueblo Viejo lagoon, a tropical coastal lagoon in Veracruz, Mexico. A total of 216 samples were collected with 329 individuals of D. auratus and 170 of E. melanopterus. Diapterus auratus individuals were captured throughout a wider range of environmental conditions, and consequently its spatial niche breadth was significantly greater (P < 0.001) than that of E. melanopterus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
1
20
1
8
Order By: Relevance
“…argenteus, as well as other Gerreidae, are omnivores and daytime feeders (KERSCHNER et al, 1985;AGUIRRE-LEÓN;YÁÑEZ-ARANCIBIA, 1986;CASTILLO-RIVERA, 2005). However, their occurrence in the present study was greater at night, both in the summer and winter, meaning that their capture did not reflect the period of greatest feeding activity.…”
Section: Discussioncontrasting
confidence: 53%
“…argenteus, as well as other Gerreidae, are omnivores and daytime feeders (KERSCHNER et al, 1985;AGUIRRE-LEÓN;YÁÑEZ-ARANCIBIA, 1986;CASTILLO-RIVERA, 2005). However, their occurrence in the present study was greater at night, both in the summer and winter, meaning that their capture did not reflect the period of greatest feeding activity.…”
Section: Discussioncontrasting
confidence: 53%
“…A member of this family is Diapterus auratus, the Irish Pompano or Mojarra Guacha. In Mexico, this species, is one of the most abundant species of the Southern part of the Gulf of Mexico and is an important part of the commercial fisheries (Castillo-Rivera et al 2005). However, in spite of their abundance, studies of their biology and anatomy are scarce (Kobelkowsky 2004).…”
mentioning
confidence: 99%
“…The fifth species (E. argenteus) was widely distributed being common in the two estuarine zones. Castillo-Rivera et al (2005) found the Gerreidae E. melanopterus and D. auratus in a protected coastal lagoon where the salinity changed between 0.5 and 33 throughout the year. The wide coastal area in the lower estuary is hardly limiting the distribution of E. brasilianus and E. melanopterus in these reaches.…”
Section: Discussionmentioning
confidence: 96%